Behavior of circular stainless steel stub columns internally strengthened by longitudinal carbon steel bars. (15th November 2019) - Sharif, Alfarabi M.; Al-Mekhlafi, Galal M.; Al-Osta, Mohammed A.
Highlights: Performance of stainless steel columns strengthened by carbon steel bars investigated. FE modeling captured the experimental response reasonably well. ACI, Eurocode 4 and CSM design models assessed using experimental and FEM results. Abstract: In this paper, experimental and numerical investigations into the performance of circular unfilled and concrete filled stainless steel tubular stub columns strengthened by carbon steel bars welded to the inner surface were presented. The carbon steel bars were fabricated to be a structural component of the stub column and directly participate in supporting the axial load. Ten stub columns of 141.3 mm outer diameter and 3.4 mm thickness were tested under axial compression load for different numbers and sizes of carbon steel bars. 3D finite element models (FEMs) were carried out for the strengthened stub columns by using finite element program ABAQUS and validated with the experimental results. The validated numerical work was utilized to carry out a parametric study to assess (i) the practical configuration of the carbon steel bars, (ii) the possible reduction of stainless steel thickness, which can be compensated for by the addition of carbon steel bars, (iii) the effect of the diameter to thickness ratio (D/t) on the stub column performance. The numerical work was further utilized to generate extensive data to validate the load carrying capacity predicted by the ACI and Eurocode4 codes and the continuous strength method (CSM). The experimental and numerical results demonstrated that this strengthening technique enhanced the axial load carrying capacity for unfilled and filled stainless steel stub columns. The results from the parametric study confirmed that (i) strengthening by two carbon steel bars is the most practical configuration to minimize the welding process, (ii) a substantial reduction in stainless steel thickness can be achieved by using carbon steel bars, (iii) the ultimate load carrying capacity is inversely proportional to the D/t ratio. CSM was the most accurate method for predicting the failure load of the strengthened stainless steel tube.